Importancia de la actividad experimental en la formación del docente de ciencias naturales - Yovana Alexandra Grajales-Fonseca; César Augusto Gutiérrez-Salazar; Audin Aloiso Gamboa-Suárez (Mundo Fesc)
This article is derived from the research "Self-authorship of intercultural texts for teaching science," conducted at the University of Santiago de Cali, Colombia. The document shows the design of experimental activities based on the thinking of future science graduates about Bernoulli's principle. Three intervention moments are designed: the first, titled "Thinking," which takes into account the student's common sense regarding this topic as a first step; the second, titled "Communication, Interpretation, and Action," where the student has the opportunity to communicate, interpret, and simulate it; and finally, a parallel is drawn between the interpretation of the same from its scientific basis in contrast to the common knowledge that is maintained. From the above, a model is proposed for the construction of school scientific knowledge through experimentation, divided into four stages. This implies a basis for new educational proposals in natural sciences based on experimental activities.